2012
DOI: 10.1111/j.1467-7687.2011.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for late maturation of strategic episodic retrieval processes

Abstract: Improvement in source memory performance throughout development is thought to be mediated by strategic processes that facilitate the retrieval of task-relevant information. Using event-related potentials (ERPs), we examined developmental changes in these processes during adolescence. Adolescents (13-14 years) and adults (19-29 years) completed a memory exclusion task which required the discrimination between words studied in one color ('targets') and words studied in the alternative color ('non-targets') under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 64 publications
(99 reference statements)
5
24
0
Order By: Relevance
“…The early old/new effect was present only for non-targets in the young, but for both conditions in the older group. In their developmental study, Sprondel et al [33] observed an unexpected frontal positive-going old/new effect in their young adults which shared some features with the present findings, being present only for non-targets, although it occurred after the mid-frontal effect, overlapping temporally with their LP effect (500–700 ms). Finding that this effect was larger in higher-WMC young adults, the authors proposed that it reflected relatively early cue-specification processes used to discriminate between targets and non-targets.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The early old/new effect was present only for non-targets in the young, but for both conditions in the older group. In their developmental study, Sprondel et al [33] observed an unexpected frontal positive-going old/new effect in their young adults which shared some features with the present findings, being present only for non-targets, although it occurred after the mid-frontal effect, overlapping temporally with their LP effect (500–700 ms). Finding that this effect was larger in higher-WMC young adults, the authors proposed that it reflected relatively early cue-specification processes used to discriminate between targets and non-targets.…”
Section: Discussionsupporting
confidence: 87%
“…We also expected that in young adults, recollection selectivity would be greater in individuals with greater WMC, replicating Elward, Wilding and others’ findings [28,30]. Critically, we predicted that the relation between WMC and recollection selectivity would not be observed in the older adults, converging with findings from other populations with reduced attentional control [30,33], and supporting the proposal that older adults fail to engage attentional resources in order to control recollection. This would also provide further support for the involvement of proactive attentional control in pre-retrieval control of episodic memory.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, this apparently had no impact on the LPN. There is also evidence from other studies that task difficulty (or the efficiency with which task-relevant attribute conjunctions can be recovered) does not necessarily affect the LPN amplitude (Sprondel, Kipp, & Mecklinger, 2012).…”
Section: Behavioral Effectsmentioning
confidence: 95%